Use of Resorbable Plate and Screws in Pediatric Craniofacial Reconstructive Surgery - Kreshanti, Prasetyanugraheni; Handayani, Siti; Bangun, Kristaninta; Tiza, Melina (Lingkar Studi Bedah Plastik Foundation, 2013)
Background: To evaluate two pediatric patients with syndromic craniofacial anomaly that underwent craniofacial reconstructive surgery using resorbable plate-screw systems which have been claimed as biodegradable fixation materials and used in craniofacial reconstructive procedures owing to their advantages such as adequate biomechanical resistance, longer dwelling time, elimination through physiological routes without causing any foreign body reaction and/or significant sequale. Patient and Method: Resorbable plate-screw systems used in 2 patiens for craniofacial reconstructive procedures such as bilateral fronto-orbital advancement and segmental right orbita (four wall box) osteotomy were evaluated as for their efficacy. Result: Adequate fixation was obtained in both patient, but Infection complication was seen in segmental right orbita osteotomy patient that appear localized abcess formation on subciliary incision and fronto medial insicion. After drainage insicion and antibiotic administration for 1 week, the infection was relieved. Summary: Owing to resorbable copolymer which contain a polyester derivate of L- lactidc and glycolic acid are ideal fixation materials used favourably in pediatric craniofacial reconstructive surgery and have further advantages such as adequate biomechanical resistance against distraction and compression forces in the early postoperative period, longer dwelling time and elimination from the body through physiological routes without causing any foreign body reaction.